THE NEW NORMS FOR HOUSEHOLD SOLID WASTE MANAGEMENT IN TIME OF COVID-19: MALAYSIAN LEGAL PERSPECTIVE (International Seminar on Syariah and Law (INSLA), 2020)
Many countries, including Malaysia, have been affected by the Covid-19 pandemic which was newly discovered at the end of 2019. Malaysia is taking steps to enforce Movement Control Order starting March 2020 and, the latest is the enforcement of the Recovery Movement Control Order until the end of this year. Covid-19 poses new challenges to waste management whereby a failure in managing wastes in the time of facing this pandemic will cause adverse effects on public safety and health as well as the environment. Hence, the relevant authorities and the public should manage waste carefully and effectively. The households may generate household hazardous solid waste such as contaminated face masks or other household solid wastes during the pandemic which must be properly disposed of. By employing a library research method and interview, this paper discusses from the legal perspective, the new norms for household solid waste management in the time of Covid-19. The findings seem to suggest that the new norms in respect of the household are seen in terms of the increased practice of 3R and separation of waste and the implementation of Standard Operating Procedures in managing household solid waste by the relevant authorities. It is recommended that households should be provided with a comprehensive guideline on household solid waste management during the pandemic of Covid-19.